After Sales as Foreign Customer Loyalty: A Perspective from Dealers of the Automotive Sector - Terres , Diane; Lazzari, Fernanda; Verruck, Fábio (Journal of Sustainable Competitive Intelligence, 2022)
Purpose: To analyze the after sales activities to get the foreign customer loyalty, as well as its operation in international markets, in the perspective of dealers of the automotive sector. Methodology/approach: Qualitative research of exploratory nature, through interviews with service providers from several countries. Originality/Relevance: Considered by several companies as a market need, after sales department, if it is well organized, works as one of the most effective tools for customer loyalty. Key findings: The results pointed after sales as a great ally of the sales department, being determinant to customer´s decision of the brand at purchasing. However, in the scope of international trade, difficulties in after sales service were noted, as well as the challenge of competing with the alternative market, highlighting the importance of managerial strategies and the construction of a solid relationship between company and client for retention and loyalty of consumers. Theoretical/methodological contributions: This paper reveals the importance of the after sales department in the international market, customer expectations, execution difficulties, as well as analyzing elements related to customer loyalty right after purchase order placement.